Comparing Arabidopsis receptor kinase and receptor protein-mediated immune signaling reveals BIK1-dependent differences - Wan, Wei-Lin; Brugman, Rik; Großmann, Guido (The new phytologist, 2019)
Pattern recognition receptors (PRRs) sense microbial patterns and activate innate immunity against attempted microbial invasions. The leucine-rich repeat receptor kinases (LRR-RK) FLS2 and EFR, and the LRR receptor protein (LRR-RP) receptors RLP23 and RLP42, respectively, represent prototypical members of these two prominent and closely related PRR families. We conducted a survey of Arabidopsis thaliana immune signaling mediated by these receptors to address the question of commonalities and differences between LRR-RK and LRR-RP signaling. Quantitative differences in timing and amplitude were observed for several early immune responses, with RP-mediated responses typically being slower and more prolonged than those mediated by RKs. Activation of RLP23, but not FLS2, induced the production of camalexin. Transcriptomic analysis revealed that RLP23-regulated genes represent only a fraction of those genes differentially expressed upon FLS2 activation. Several positive and negative regulators of FLS2-signaling play similar roles in RLP23 signaling. Intriguingly, the cytoplasmic receptor kinase BIK1, a positive regulator of RK signaling, acts as a negative regulator of RP-type immune receptors in a manner dependent on BIK1 kinase activity. Our study unveiled unexpected differences in two closely related receptor systems and reports a new negative role of BIK1 in plant immunity.
First published: 25 September 2018
Gesehen am 02.05.2019